2012
DOI: 10.1109/taes.2012.6324744
|View full text |Cite
|
Sign up to set email alerts
|

Joint Detection, Tracking, and Classification of Multiple Targets in Clutter using the PHD Filter

Abstract: To account for joint detection, tracking, and classification (JDTC) of multiple targets from a sequence of noisy and cluttered observation sets, this paper introduces a recursive algorithm based on the probability hypothesis density (PHD) filter with the particle implementation. Assuming that each target class has a class-dependent kinematic model set, a class-matched PHD-like filter (i.e., PHD filter or its multiple-model implementation (MMPHD)) is assigned to it. In the prediction stage, the particles are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…Considering extensions to different target types, Yan et al [25] developed detection, tracking and classification (JDTC) of multiple targets in clutter by jointly estimating the number of targets, their kinematic states, and types of targets (classes) from a sequence of noisy and cluttered observation sets using a SMC-PHD filter. The dynamics of each target type (class) was modeled as a class-dependent model set and the signal amplitude was included in the multi-target likelihood to enhance the discrimination between targets from different classes and false alarms.…”
Section: Related Workmentioning
confidence: 99%
“…Considering extensions to different target types, Yan et al [25] developed detection, tracking and classification (JDTC) of multiple targets in clutter by jointly estimating the number of targets, their kinematic states, and types of targets (classes) from a sequence of noisy and cluttered observation sets using a SMC-PHD filter. The dynamics of each target type (class) was modeled as a class-dependent model set and the signal amplitude was included in the multi-target likelihood to enhance the discrimination between targets from different classes and false alarms.…”
Section: Related Workmentioning
confidence: 99%
“…2. it can be shown that the posterior intensity can be propagated over time according to the following PHD recursion [13]. First, given the previous state ξ ∈ X , the intensities are mixed so that:…”
Section: A Multiclass Mm-gmphd Filtermentioning
confidence: 99%
“…In [122], the distribution of the particles is fitted using finite mixture models (FMMs), whose parameters can be derived using a MCMC sampling scheme, then the states can be extracted according to the fitted mixture distribution. In [123], a flexible modularized structure for SMC-PHD filter is introduced, and the particles with the same class label and their corresponding weights represent the estimated class-conditioned PHD distribution. The mathematical proofs of convergence for the SMC algorithm and gives bounds for the mean-square error is presented in [124].…”
Section: Implementation Of Fisst Based Filtersmentioning
confidence: 99%